2018
DOI: 10.3389/fped.2018.00360
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences Between Staphylococcal and Streptococcal Toxic Shock Syndromes in Children: Results From a 30-Case Cohort

Abstract: Introduction: Toxic shock syndromes (TSS) are severe shocks due to staphylococcal or streptococcal infection that require specific treatments. The early recognition of these shocks is crucial to improve their outcomes.Objectives: The primary objective of this study was to compare characteristics and outcomes of staphylococcal and streptococcal TSS in children, in order to identify putative early clinical diagnostic criteria. Secondary objectives were to determine the toxin gene profiles of associated isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
4
20
1
Order By: Relevance
“…Our results of a Vβ2-specific response to GAS superantigens, as well as TSST-1, is of particular importance considering that skewed Vβ profiles, involving either expansion or depletion of Vβ2-expressing CD3 + cells, have been reported in superantigen-associated toxic shock cases caused by either S. aureus or GAS (7, 8, 41). Taken together, with Vβ2 being the dominant Vβ expressed by human MAIT cells, this provides an explanation to the high frequency of superantigen-triggered cytokine production in MAIT cells compared with the total CD3 + compartment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our results of a Vβ2-specific response to GAS superantigens, as well as TSST-1, is of particular importance considering that skewed Vβ profiles, involving either expansion or depletion of Vβ2-expressing CD3 + cells, have been reported in superantigen-associated toxic shock cases caused by either S. aureus or GAS (7, 8, 41). Taken together, with Vβ2 being the dominant Vβ expressed by human MAIT cells, this provides an explanation to the high frequency of superantigen-triggered cytokine production in MAIT cells compared with the total CD3 + compartment.…”
Section: Discussionmentioning
confidence: 58%
“…Superantigen involvement in patients with STSS was proposed by studies on peripheral blood demonstrating a skewed Vβ repertoire in T cells during the acute phase (68). Only limited data are available on the cytokine responses in patients, but an initial report by Sriskandan et al (9) demonstrated elevated levels of TNFβ (lymphotoxin-α).…”
mentioning
confidence: 99%
“…Considering that neither SEG and SEI nor SSA showed significant differences when human monocytes were treated with them, we could suggest that this first step of infection, which is essential for bacterial dissemination and the subsequent disease prognosis, does not explain the discrepancy of progression to the TSST observed among toxins belonging to different species (66). Nevertheless, it is clear that TSS involves other components of the pathogens which are not evaluated in the present work.…”
Section: Discussionmentioning
confidence: 65%
“…Asterisks represent statistical significance with respect to the untreated cells in each treatment: ****p < 0.0001, ns, non-significant difference. Hashes represent statistical significance with respect to cells treated only with SAgs in each treatment: #### p < 0.0001. staphylococcal and streptococcal TSS differ in their clinical signs, origin of infection, and prognosis (66,78). In order to elucidate if egc SAgs and SSA shared comparable effects on innate immune system cells, we studied both types of toxins.…”
Section: Discussionmentioning
confidence: 99%
“…7 STSS is a complication in 2%-15% of children (vs. 3%-28% in adults) and can carry a CFR of up to 28%. [8][9][10] The principal sites of iGAS infection in children are the skin and the lungs. 2,11,12 Other iGAS clinical syndromes include osteoarthritis and meningitis, which, although rare, are more common in children than in adults.…”
mentioning
confidence: 99%